Membangun loyalitas pelanggan melalui kualitas produk dan citra merek (studi pada pelanggan Oppo Jambi) - Afrida, Resi; Yacob, Syahmardi; Sari, Novita (Jurnal Dinamika Manajemen, 2020)
This study aims to analyze the quality of products and brand image of customer loyalty either partially or simultaneously. The number of samples in this study was 99 respondents. The type of research used is explanatory research while hypothesizing using multiple linear regression. Customer loyalty is influenced by brand image through product quality. However, other factors that influence customer loyalty and brand image, and product quality need to be continued by further research to increase customer loyalty from different perspectives.